Kepercayaan Epistemologis dan Faktor-faktor yang Memengaruhinya - M. Nur Ghufron; Asmadi Alsa; Yapsir Gandhi Wirawan (Jurnal Psikologi, 2013)
This research aimed to: (1) finding out whether there was conformity between the theoretical model of factors affecting students’ epistemological beliefs and the empirical models, (2) assessing whether interdependent self-construal, level of education, constructivist learning environment and metacognition predicted of epistemological beliefs as measured by belief about knowledge and belief about learning, (3) assessing whether interdependent self-construal, level of education, constructivist learning environment and metacognition predicted of epistemological beliefs as measured by belief about knowledge and (4) assessing whether interdependent self-construal, level of education, constructivist learning environment and metacognition predicted of epistemological beliefs as measured by belief about learning.The population in this research consists of the first to eight semesters students of “X” Department of STAIN Kudus , Central Java. The sample was as many as study 268 students, taken through stratified random sampling method. The data collection techniques used in this research was questionnaire in the form of scales and checklists.The data were analyzed using Structural Equation Models (SEM). The research resulted: (1) The (theoretical model) designed in the research is proper, and conforms with the data collected (empirical model), (2) The determination (R²) of the students’ epistemological beliefs is 0.80, which means that 80 percent of epistemological beliefs can be explained or predicted through the variables of interdependent self-construal, level of education and constructivist learning environment, (3) The determination (R²) of the students’ beliefs about knowledge is 0.52, which means that 52 percent can be explained or predicted through the variables of interdependent self-construal, level of education and constructivist learning environment, (4) The determination (R²) of the students’ beliefs about learning is 0.28, which means that 28 percent can be explained or predicted through the variables of interdependent self-construal, level of education and constructivist learning environment. Based on this research, examine the importance of epistemological beliefs as a basic foundation of education, it is necessary for educators to examine these factors in the teaching and learning process. Keywords: epistemological beliefs, interdependent self-construal, level of education, constructivist learning environment and metacognition